2015
DOI: 10.1073/pnas.1523148113
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into c-di-GMP–dependent control of the biofilm regulator FleQ fromPseudomonas aeruginosa

Abstract: Bacterial biofilm formation during chronic infections confers increased fitness, antibiotic tolerance, and cytotoxicity. In many pathogens, the transition from a planktonic lifestyle to collaborative, sessile biofilms represents a regulated process orchestrated by the intracellular second-messenger c-di-GMP. A main effector for c-di-GMP signaling in the opportunistic pathogen Pseudomonas aeruginosa is the transcription regulator FleQ. FleQ is a bacterial enhancer-binding protein (bEBP) with a central AAA+ ATPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
205
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(212 citation statements)
references
References 63 publications
5
205
0
2
Order By: Relevance
“…In Streptomyces, c-di-GMP mediates the switch from vegetative growth to sporulation through its binding to the transcriptional repressor BldD (20). In Pseudomonas, c-di-GMP binding to the NtrC-like protein FleQ results in stimulation of pel transcription (21)(22)(23). In Klebsiella pneumoniae, the PilZ domain-containing transcriptional activator MrkH activates genes for fimbriae synthesis upon c-di-GMP binding (24).…”
mentioning
confidence: 99%
“…In Streptomyces, c-di-GMP mediates the switch from vegetative growth to sporulation through its binding to the transcriptional repressor BldD (20). In Pseudomonas, c-di-GMP binding to the NtrC-like protein FleQ results in stimulation of pel transcription (21)(22)(23). In Klebsiella pneumoniae, the PilZ domain-containing transcriptional activator MrkH activates genes for fimbriae synthesis upon c-di-GMP binding (24).…”
mentioning
confidence: 99%
“…Thus, a full activity of FlrA to repress the transcription of bpfA involves both of the binding sites of box 1 and box 2. c-di-GMP interferes with the binding of FlrA to the promoter of bpfA. FleQ, an FlrA ortholog in Pseudomonas aeruginosa, functions as a c-di-GMP-responsive regulator, and its residues involved in the biding of c-di-GMP have been characterized (30). FlrA also possesses these conserved residues (Fig.…”
mentioning
confidence: 99%
“…FlrA also possesses these conserved residues (Fig. S5) (30), which suggests that the activity of FlrA may be tuned by c-di-GMP, a second messenger found in many bacteria (31). We first tested the effect of c-di-GMP on the binding of FlrA to the FlrA box ib bpfA promoter region in vitro via fluorescence polarization (FP).…”
mentioning
confidence: 99%
“…Because several PilR-type transcription regulators, e.g., FleQ from P. aeruginosa (29,30) and XbmR from Xanthomonas citri (31), have been shown to bind c-di-GMP directly, (25). ΔpilR(pURF047), the ΔpilR mutant containing an empty vector; ΔpilR(pilR-cp2), the ΔpilR mutant with plasmid pilR-pUFR047, containing the intact pilR gene.…”
Section: Resultsmentioning
confidence: 99%
“…The PilR-mediated regulation of HSAF production turned out to be indirect and independent of the regulation of T4P genes. Because several NtrC-type RRs to which PilR belongs, including P. aeruginosa FleQ (29,30) and X. citri XbmR (31), bind c-di-GMP directly, in this work we tested L. enzymogenes PilR for c-di-GMP binding; however, no binding was detected. Intriguingly, we found that the pilR deletion resulted in elevated intracellular c-di-GMP levels, which proved to be inhibitory for HSAF production.…”
Section: Discussionmentioning
confidence: 99%